2021
DOI: 10.1088/1361-6501/ac3b09
|View full text |Cite
|
Sign up to set email alerts
|

Tomographic background oriented schlieren using plenoptic cameras

Abstract: The development of a tomographic BOS implementation system utilizing up to four plenoptic cameras is presented. A systematic set of experiments was performed using a pair of solid dimethylpolysiloxan (PDMS) cylinders immersed in a nearly refractive index matched gylcerol/water solution to represent discrete flow features with known sizes, shapes, separation distances, and orientation. A study was conducted to assess the influence of these features on the accuracy of 3D reconstructions of the refractive index fiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Historical studies have shown that a single plenoptic camera in conventional plenoptic BOS systems is not sufficient for accurate BOS reconstruction [38]. Therefore, recent studies have explored plenoptic BOS systems based on multi-camera tomography technology and single-camera mirror-enhanced dual-view to achieve higher-accuracy 3D density field reconstruction, respectively.…”
Section: Multi-view Plenoptic Bos Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…Historical studies have shown that a single plenoptic camera in conventional plenoptic BOS systems is not sufficient for accurate BOS reconstruction [38]. Therefore, recent studies have explored plenoptic BOS systems based on multi-camera tomography technology and single-camera mirror-enhanced dual-view to achieve higher-accuracy 3D density field reconstruction, respectively.…”
Section: Multi-view Plenoptic Bos Imagingmentioning
confidence: 99%
“…Davis [38] has developed a tomographic BOS system using 1-4 plenoptic cameras and an iterative simultaneous algebraic reconstruction technique (SART) [39] algorithm to achieve the quantitative volume reconstruction of known 'static flow' fields. The workflow starts with the calibration of the microlens [40] and volume [27].…”
Section: Tomographic Plenoptic Bosmentioning
confidence: 99%
“…5 The Advanced Flow Diagnostic Laboratory (AFDL) at Auburn University has demonstrated the ability to perform 3D reconstructions with a reduced number of cameras for particle image velocimetry (PIV), 2 particle tracking velocimetry (PTV), 6,7 and tomographic background oriented schlieren (Tomo-BOS). 8 Combustion processes are very complex with multiple reactions, oscillations, and potentially turbulent flow fields with multiscale features throughout the flow. All of these can effect the behavior of the combustion.…”
Section: Introductionmentioning
confidence: 99%